Coronary sinus reducer for the treatment of chronic refractory angina pectoris‐results of the preclinical safety and feasibility study. Issue 7 (30th September 2018) - Konigstein, Maayan; Shofti, Rona; Schwartz, Marc; Banai, Shmuel
Abstract: Background: Narrowing of the coronary sinus (CS) has recently emerged as a new therapeutic option for the treatment of patients with chronic refractory angina pectoris. The results of the preclinical study presented here, evaluate the safety, feasibility, and efficacy of reducer implantation in a swine model with and without myocardial ischemia. Methods and results: The study included a safety/feasibility arm, and a safety/efficacy arm. In the safety/feasibility arm, reducers were implanted in 26 mini swine; follow up of up to 6 months included cardiac catheterization with CS angiogram, and histological evaluation of the stented segments of the CS. In the safety/efficacy arm, eight swine with evidence of inducible myocardial ischemia were divided into reducer implantation group ( n  = 4) and a control group ( n  = 4). Follow‐up in this arm included 6 weeks and 6 months dobutamine stress echo and myocardial contrast echo to evaluate severity and extent of ischemia. In the safety/feasibility arm ( n  = 26), reducers were implanted with procedural success rate of 100% and with no short or long‐term complications. All CS reducers were found to be patent at the time of sacrifice. In the safety/efficacy arm, all four animals with myocardial ischemia that underwent reducer implantation showed improvement in ischemia parameters at 6 weeks and 6 months follow‐up, with no mortality. Among the control group, no improvement in ischemia parameters was observed and three out of four animals died. Conclusions: Narrowing of the CS using percutaneous implantation of the reducer in swine is feasible, safe, and improves the extent and severity of ischemia.